Lactantius' Adaptation and Rejection of Lucretius De rerum natura 1.936–50. - Keil, Matthew A. (Classical Philology, 2021)
A growing number of scholars in recent decades have begun to appreciate Lactantius' interaction with Lucretius on the level not only of language and poetics, but one which also reveals a careful and profound study of the Roman poet's epic. The present discussion addresses the hitherto unnoticed point about Lactantius' adaptation of Lucretius' famous wormwood simile, that it entails a utilization of the same polemical method that Lucretius himself employs when adopting the language and style of his philosophical opponents.